The emergence of contemporary criminology: an oral history of its development as an independent profession - Dooley, Brendan D. (Crime, law and social change, 2016)
Criminology, as an independent academic pursuit, has maturated to the point where it is now interested in exploring its genealogy. Larger soio-political developments evidenced a pattern of influence in terms of promoting ideas and building the field’s infrastructure. The field’s growth from its early professionalization is documented here through an analysis of oral histories offered by seventeen influential scholars. Respondents explained their respective journeys to the field via three avenues: biographical, intellectual, and through the graduate school experience. Four scholars spoke to the emotive elements that attracted them to the field. The remainder sought answers to nagging questions on either empirical or theoretical matters. Lastly, the semi-structured interviews elicited accounts of their respective graduate school curricula and the role of mentoring. The essential lesson to be drawn from the collective experience is that the graduate school experience should include exposure to the broader liberal tradition and on the history of the field.